A cross-sectional matched sample study of nonsuicidal self-injury among young adults: support for interpersonal and intrapersonal factors, with implications for coping strategies. Issue 1 (December 2015) - Trepal, Heather; Wester, Kelly; Merchant, Erin
Abstract Background Young adults are a high-risk group for nonsuicidal self-injury (NSSI). It is important to have a better understanding of these behaviors in order to facilitate effective research, intervention, and treatment. Models have been presented to explain these behaviors where emotion regulation, coping, and support play a role. Yet conflicting results have occurred based on demographic factors such as race and sex. While controlling for the observable demographic factors, this study sought to examine differences between individuals who currently engage in NSSI, engaged in NSSI in the past, and never engaged in NSSI related to emotions, coping strategies, interpersonal support, and ethnic identity and belonging. Methods Participants were selected from freshman students at two universities, in geographically different locations in the United States (N  = 282). Participants in this study were matched on demographic factors: race, sex, and university. This led to demographically matched groups (current, past, never engagement in NSSI;n  = 94 per group). Groups were compared on intrapersonal factors (i.e., emotions: depression and anxiety; coping strategies: adaptive and maladaptive; interpersonal support: family, friend, and significant other; and ethnic identity and belonging). Descriptive statistics and ANOVA with post hoc Scheffe were utilized to explicate differences between groups. Results Individuals who never engaged in NSSI reported significantly higher levels of ethnic belonging and interpersonal support and lower levels of depression and anxiety than both groups who engaged in NSSI. Individuals who never self-injured used less adaptive and maladaptive coping strategies than participants who self-injured. Young adults who currently engaged in NSSI reported higher levels of depression and anxiety, higher levels of both types of coping, and perceived less support. Conclusions It is important to understand the differences between individuals who self-injure in comparison to those who do not so that mental health clinicians can provide more effective services and preventative efforts.